PILKADA, DINASTI POLITIK DI ERA DESENTRALISASI (STUDI TENTANG HABITUS AND FIELD, AKTOR POLITIK DALAM KONTESTASI PILKADA KAB. BANGKALAN YANG MELAHIRKAN DINASTI POLITIK) - Rachman, Yudhi (DIMENSI, 2015)
This Thesis attempts to capture the power developed in an area aftermath of reformation era in 1998 marked by implementing autonomous region or decentralized. Power in The New Order Regime, that was The Centralistic changed with the emergence of the local political elite that affirming their power by various sources of capital.Â By having a more open space for local figures to snatch the seat of power at the local level in the county, political competition then became closer in social community base level. Those who have a culture of social capital, networks and other social networking might be easier to perform. No exception figure of âKiaiâ head of Islamiccommunity originating from habitus religious activities and education in boarding school and other community social activities.In Bangkalan regency Habitus-based Political Elite Kiai boils down to descendants of the BaniKholildiasporic in various organizations either initiating Community-Social Organizations, political parties and legislative Institutions and Executive.The method used in this research is descriptive-qualitative structure of Agency Bourdieus approach with data mining using in-depth interviews and technical documentation.Â The end result of this thesis was to see that the political and Dynastic Politics Breeds successfully built by RKH Fuad Amin during his leadership in two periods, ten years later continued by the winning of his son MakmunIbnuFuad with a majority of votes 93,47 percent. After his main rival who is also a descendant of BaniKholil, namely KH Imam BuchoriKholil failed to follow the contestation elections directly.In contestation elections in Bangkalan Regency, the ability of the group or Political Actor in using sources of capital and symbolic power in a society is still very effective in managing their Paternalistic room practices.In the analysis of Structure-Agency Bourdieus perspective, social space and social groups who control it are the products of a historical struggle continuously updated for contested or won as well as establish dominance in power.